Effect of lettuce biofortified with iodine by soil fertilization on iodine concentration in various tissues and selected biochemical parameters in serum of Wistar rats. (April 2015) - Kopeć, Aneta; Piątkowska, Ewa; Bieżanowska-Kopeć, Renata; Pysz, Mirosław; Koronowicz, Aneta; Kapusta-Duch, Joanna; Smoleń, Sylwester; Rakoczy, Roksana; Skoczylas, Łukasz; Leszczyńska, Teresa; Ledwożyw-Smoleń, Iwona
Highlights: The effect of lettuce biofortified with iodine was evaluated in rats. Iodine from lettuce is bioavailable for rodents. Content of iodine increased in various tissues of rats fed biofortified lettuce. Biofortified lettuce can be a good source of iodine in daily diets. Abstract: In this study, for the first time, we evaluated the effect of lettuce biofortified with iodine on iodine content in various tissues and selected biochemical parameters in the serum of Wistar rats. Significantly higher concentrations of iodine were measured in urine, faeces, hearts, and kidneys of rats fed the control diet (C diet) and the diet containing biofortified lettuce (BFL) compared to rats fed a diet containing non fortified-control lettuce or a diet with a lower level of iodine (equal to the content in control lettuce). Significantly higher concentrations of iodine were measured in the liver and femoral muscle of rats fed the BFL diet compared to the other experimental groups. Thyroid hormones, thyroid stimulating hormone, aspartate aminotransferase, alanine aminotransferase and selected genes' mRNA activities were not affected by the presence of biofortified lettuce in the diet compared to the control group. Biofortified lettuce may be considered as a potential source of iodine in the prevention of deficiency of this trace element.